Дружка в севернорусской свадьбе: о некоторых условиях выбора и атрибутах - Крашенинникова Ю. (Народна творчість та етнографія, 2007)
This article is dedicated to the role that the best man is playing in Russian (specially, Russian North) wedding tradition. The author is analysing the role of the best man through the most popular attributes and conditions on which the best man was chosen for the wedding ritual. The informants are people born between 1930 and 1930s in Archangelsk, Kirov Regions and in the Republic of Komy. The best man according to the informants was supposed to know the wedding “text”, know how to direct the ritual, to create dialogues with the wedding ritual participants and their attributes were the wedding towel, the belt, the bandage, the ring, the broom, that would distinguish them from the other participants. A towel played a special symbolic role on the best man’s arm. All those things played a protective role as well.